Kontribusi Kondisi Fisik Lingkungan Rumah dengan Kejadian Diare dan Hubungannya terhadap Kejadian Stunting - Lestari, Marliana Eka Puji; Siwiendrayanti, Arum (Indonesian Journal of Public Health and Nutrition, 2021)
Background: Stunting is a priority problem in the working area Puskesmas Pecangaan, Jepara. Based on data of August 2020, 183 toddlers with severely stunted cases, and 536 toddlers with stunted cases. The factors stunting can be seen from the aspect environmental hygiene, so that it can increase the risk of diarrhea. The purpose of this study was to determine the contribution physical condition of the home environment to diarrhea and its relationship to stunting. Methods: Observational analytic with case control design. The samples needed was 68 toddlers. The instrument used a questionnaire and observation sheet. Data analysis using chi-square statistical test. Results: There is relationship between the condition of drinking water sources and diarrhea (p=0.007), there is no relationship between physical water quality and diarrhea (p=0.090), there is relationship between latrine conditions and diarrhea (p=0.032), there is relationship between type of house floor and diarrhea (p=0.014), and there is relationship between diarrhea and stunting (p=0.007). Conclusion: There is a contribution of condition of drinking water sources, latrine conditions, and type of house floor to diarrhea. Diarrhea is related to stunting. And there is no contribution of physical water quality to diarrhea.